Changes in the distribution of marine invertebrates in a warming Barents Sea over the last century - Calvet, Nathalie (UiT Norges arktiske universitet, 2023)
The Barents Sea is a shelf sea in the European Arctic and is influenced by the North Atlantic Current and the Arctic Ocean. The North Atlantic Current is composed of warmer, saline waters compared to the cold, fresher waters from the Arctic Ocean. Over the last century, the Barents Sea mean temperature has increased by 1.5°C above a depth of 60m and by 0.5-0.8°C below 60m. This warming is disproportionately high compared to other areas of the globe. A consequent loss of sea ice and changes in the salinity of the Arctic Ocean has been observed, especially since the 1980s. It is important to monitor distribution changes in marine invertebrates because they can reflect fluctuations of their environment and can potentially have strong impacts on the ecosystem. Marine invertebrates occupy many ecological niches and go through diverse life stages, including external fertilisation and often a planktonic larval stage. They are therefore dependent on environmental conditions both in the benthos (in case of seafloor dwellers) and the water column. For example, those with a planktonic life stage are distributed by marine currents and each species has a temperature and salinity optimum for their development. It is therefore expected that changes in the environment, such as increased ocean temperatures due to climate change, will lead to changes in the distribution of marine organisms. However, changes of invertebrates’ distributions in the Barents Sea over the entire past century have not been studied yet and this is the objective of this study. I used data mediated by the Global Biodiversity Information Facility (GBIF) to characterize species distributions and their potential change over more than a hundred years. The periods were separated into five blocks starting before 1900 and go until 2010. I took the acceleration of the warming past 1980 into account by shortening the later time ranges. The study area was divided into warm (south-western Barents Sea), mixed (central Barents Sea) and cold (North-eastern Barents Sea) ...